Identities Characteristic of Teachers in Catholic Schools. - Rungrojworawatana, Disapon; Kulophas, Dhirapat (Saengtham College Journal, 2021)
The objectives of this research were to study the Identities Characteristic of Teachers in Catholic Schools. The primary qualitative data consists of 7 documents published by the Sacred Congregation for Catholic Education. The research instrument was a document analysis form. Data analysis methods were content analysis by classification and inductive conclusion. The results reveal that there were 7 Identities characteristic of Teachers in Catholic Schools, consisted of 1) living to testify of Christ, 2) awareness and dedication to the duty of a teacher, 3) joining every part of the community, 4) preparing and developing of secular knowledge, 5) being an expert in teaching moral and religious teachings, 6) being a person who capable of synthesizing, combining beliefs, culture, and life, 7) developing of spiritual life with each student directly and individually. Teachers in Catholic Schools might recognize the need to keep themselves following these identities and might receive continuous support in developing them from the school directors, executive director, and authority organization to maintained Catholic Identities in their school and achieve the goal of promoting students to be perfect human beings.